Konsep Manusia dan Pembentukan Akhlak dalam Pemikiran Ibn Miskawayh: Perspektif Filsafat Pendidikan Islam - MUHAMAD AFIFFUDIN; mungkassifurahman; akin mustakin; akhmad fauzi; a heris hermawan (JURNAL PENA, 2026)
This study aims to analyze the concept of humankind in Ibn Miskawayh's thought and its relevance to the formation of morality in contemporary Islamic educational philosophy. The background of this research is based on the moral crisis in the world of modern education, which tends to emphasize cognitive aspects and ignore character development. The study uses a qualitative approach with a library research type. Data were obtained from Ibn Miskawayh's main work, Tahdzib al-Akhlak wa Tathhir al-A'raq, as well as various supporting literature in the form of relevant books and scientific articles. The data analysis technique used content analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that according to Ibn Miskawayh, humans are rational and moral beings who have the potential for rational, emotional, and lustful souls that must be balanced through moral education. Moral formation is carried out through habituation, self-control, and the development of moral virtues. These findings confirm that Ibn Miskawayh's thought is relevant as a philosophical foundation in the development of Islamic education oriented towards intellectual, moral, and spiritual balance.